The social-emotional crisis of gifted children in the digital era: a theoretical review based on the anxious generation - Izzatuljannah; Syafril , Syafrimen (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Gifted children possess heightened emotional and social sensitivity, which makes them more vulnerable to psychological pressure amid changing interaction patterns driven by digitalization. This phenomenon, as articulated in The Anxious Generation, suggests that excessive digital exposure can fundamentally alter the dynamics of children’s social-emotional development. Objective: This study aims to analyze the social-emotional crisis experienced by gifted children in the digital era by integrating Jonathan Haidt’s theoretical framework to elucidate emerging vulnerability mechanisms and identify relevant directions for intervention. Method: This research employed a Systematic Literature Review of 80 national and international publications addressing giftedness and digitalization. Qualitative analysis was conducted to identify thematic patterns and examine intervariable relationships within the context of gifted children’s social-emotional development. Result: The analysis revealed three major patterns: (1) heightened emotional sensitivity increases the risk of anxiety resulting from intensive digital interactions; (2) the phenomenon of great rewiring shifts real-life social experiences toward more passive digital activities; and (3) social isolation and identity dilemmas emerge as consequences of the imbalance between advanced intellectual abilities and emotional maturity. Conclusion: Digitalization intensifies the social-emotional challenges faced by gifted children. Therefore, educational policies and psychological strategies are needed to balance cognitive stimulation with emotional well-being in order to support healthy child development in the digital era.